2009
DOI: 10.1590/s0006-87052009000400027
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação superficial de calcário e diferentes resíduos em soja cultivada no sistema plantio direto

Abstract: SURFACE APPLICATION OF LIMESTONE AND DIFFERENT RESIDUES ON SOYBEAN GROWN IN NO-TILL SYSTEMThe practice of correcting soil acidity by surface application of pH-correcting materials on crop residues in the no-till system is restricted to limestone. No further studies are available on the use of steel slag, lime mud, and centrifuged sewage sludge. The objective of this study was to evaluate soil acidity and yield of soybean as a function of surface application of centrifuged sewage sludge, lime mud, steel slag, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
15
0
6
Order By: Relevance
“…Studies conducted by [19,22,[25][26][27][28] showed positive effects in soil acidity correction of surface application of steel slag compared to lime in no-tillage system, in tropical soil.…”
Section: Steel Slag Modifying Soil Chemical Attributesmentioning
confidence: 99%
“…Studies conducted by [19,22,[25][26][27][28] showed positive effects in soil acidity correction of surface application of steel slag compared to lime in no-tillage system, in tropical soil.…”
Section: Steel Slag Modifying Soil Chemical Attributesmentioning
confidence: 99%
“…In an experiment that analyzed dolomitic LS, centrifuged SSS, aqueous lime, and SS, SS was the most effective in amendment of soil acidity (Corrêa et al 2009). Carvalho-…”
Section: Soil Nutrientsmentioning
confidence: 99%
“…Since high acidity rates characterize most soils in Brazil, soil acidity is one of the main causes of low yield, regardless of the production system (Corrêa et al, 2009;Nogueira et al, 2013). In areas with perennial crops, such as coffee plantation, acidity corrective is applied on the soil surface, although its incorporation to the soil is difficult and causes phytosanitary problems to the shrubs.…”
Section: Introductionmentioning
confidence: 99%